Perkembangan Kesenian Tradisional Buaya Putih pada Acara Pernikahan di Kampung Curugdahu Desa Kadubeureum Kecamatan Padarincang Kabupaten Serang Tahun 1992-2022 - Nofriana, Fenny; Rustamana, Agus; Ribawati, Eko (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to explain the development of White Crocodile Traditional Art at weddings in Curugdahu village Kadubeureum sub-district Padarincang district Serang Regency 1992-2022: 1) how the White Crocodile art emerged and developed, 2) how the function of the White Crocodile traditional art changed. The method used in this research is the historical method, including: heuristics, source criticism, interpretation, and historiography. The background of the birth of the traditional art of Buaya Putih is not known for certain, but it began to appear in the 1970s. The White Crocodile Traditional Art experienced development in 1992-2022. The White Crocodile Traditional Art was originally only a traditional art at weddings that functioned to parade the groom using a replica of the White Crocodile to put offerings to the 0bride's house. Along with its development, the White Crocodile art is no longer used as a traditional art for weddings, but as a mauludan event, welcoming guests, building inauguration, government anniversaries, circumcisions and entertainment shows. This shows that there is a shift in the value of functions that occur in the White Crocodile art. The influence of the traditional art of White Crocodile on the socio-cultural life in Curugdahu village, Kadubeureum village, Padarincang sub-district as a community tradition. The traditional art of White Crocodile must be preserved as a cultural identity of the people of Curugdahu Village, Kadubeureum Village, Padarincang District in order to maintain cultural values and local wisdom.